2011
DOI: 10.2217/fmb.10.165
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Mycobacterium Tuberculosis : Application in Epidemiologic Studies

Abstract: Genotyping is used to track specific isolates of Mycobacterium tuberculosis in a community. It has been successfully used in epidemiologic research (termed ‘molecular epidemiology’) to study the transmission dynamics of TB. In this article, we review the genetic markers used in molecular epidemiologic studies including the use of whole-genome sequencing technology. We also review the public health application of molecular epidemiologic tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
101
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 112 publications
0
101
0
1
Order By: Relevance
“…Basic strain classification in phylogenetic families was performed using the MIRU-VNTRplus server (22,33). To determine the spoligotype family (26), patterns were compared with those in the international database of spoligotyping patterns (http://www.miru -vntrplus.org/MIRU/index.faces) and the rules for the spoligotype family prototype (16). MIRU-VNTR profiles with double alleles at a single locus were considered to represent heterogeneous populations of the same strain, whereas those with double alleles at 2 or more loci were considered to represent mixed infections or to indicate cross-contamination (34,35).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Basic strain classification in phylogenetic families was performed using the MIRU-VNTRplus server (22,33). To determine the spoligotype family (26), patterns were compared with those in the international database of spoligotyping patterns (http://www.miru -vntrplus.org/MIRU/index.faces) and the rules for the spoligotype family prototype (16). MIRU-VNTR profiles with double alleles at a single locus were considered to represent heterogeneous populations of the same strain, whereas those with double alleles at 2 or more loci were considered to represent mixed infections or to indicate cross-contamination (34,35).…”
Section: Methodsmentioning
confidence: 99%
“…This paradox of improved TB management and worsening resistance prevalence has been explained by increases in the notified cases, i.e., in case detection, although treatment outcomes remain poor (12). Basically, the observed increases in MDR-TB rates may result from two factors, i.e., transmission of MDR-TB and acquired resistance due to ineffective TB treatment selecting for spontaneous mutations in specific genes associated with drug resistance (13,14).Molecular strain typing (genotyping) has significantly contributed worldwide to the understanding of TB epidemiology and transmission dynamics (15,16), by confirming outbreaks (17) and identifying the clonal spread of successful strains, including MDR strains (18,19). Furthermore, molecular typing has shown that the Mycobacterium tuberculosis complex (MTBc) has a diverse population structure, being composed of seven lineages of human …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MTBC isolates representing at least 28 different spoligotypes were selected based on spoligotyping information provided by the Genotyping Laboratory of the California Department of Health Services (27,28). Spoligotyping was also used to discriminate M. bovis and M. africanum from other MTBC strains.…”
Section: Methodsmentioning
confidence: 99%
“…7 Mycobacterium tuberculosis genotyping has proven to be the most important laboratory tool in understanding TB transmission. 8 In addition to studies on patient contacts; information on molecular epidemiology is useful for evaluating TB control program results. Genotyping also assists in monitoring molecular markers associated with virulence, immunogenicity, and drug resistance 9 ; among the genotyping tools available, the IS6110-restriction fragment length polymorphism (RFLP) reference standard method is based on the number of repetitions of the IS6110 sequence along the M. tuberculosis genome.…”
mentioning
confidence: 99%